Niche Differentiation of Active Methane-Oxidizing Bacteria in Estuarine Mangrove Forest Soils in Taiwan - Yo-Jin Shiau; Chiao-Wen Lin; Yuanfeng Cai; Zhongjun Jia; Yu-Te Lin; Chih-Yu Chiu (Microorganisms, 2020)
Mangrove forests are one of the important ecosystems in tropical coasts because of their high primary production, which they sustain by sequestering a substantial amount of CO2 into plant biomass. These forests often experience various levels of inundation and play an important role in CH4 emissions, but the taxonomy of methanotrophs in these systems remains poorly understood. In this study, DNA-based stable isotope probing showed significant niche differentiation in active aerobic methanotrophs in response to niche differentiation in upstream and downstream mangrove soils of the Tamsui estuary in northwestern Taiwan, in which salinity levels differ between winter and summer. Methylobacter and Methylomicrobium-like Type I methanotrophs dominated methane-oxidizing communities in the field conditions and were significantly 13C-labeled in both upstream and downstream sites, while Methylobacter were well adapted to high salinity and low temperature. The Type II methanotroph Methylocystis comprised only 10–15% of all the methane oxidizers in the upstream site but less than 5% at the downstream site under field conditions. 13C-DNA levels in Methylocystis were significantly lower than those in Type I methanotrophs, while phylogenetic analysis further revealed the presence of novel methane oxidizers that are phylogenetically distantly related to Type Ia in fresh and incubated soils at a downstream site. These results suggest that Type I methanotrophs display niche differentiation associated with environmental differences between upstream and downstream mangrove soils.